Molecular Identification and Analysis of Multi-Drug Resistant Klebsiella pneumonia - Ramasamy, Rajeswari; Subramanian, Subha Ashley Thanga; Rajagopal, R. Abinaya; Muthusamy, Karthikadevi; Johney, Jesteena; Ragunathan, R. (International Journal of Applied Sciences and Biotechnology, 2018)
Multidrug resistant Klebsiella pneumoniae was resistant to various antibiotics which are commonly used to treat against the bacterial infections, and is now emerged as a great risk. Antibiotic susceptibility tests were performed to determine the scope of drug resistance of the bacteria. Further studies regarding the responsible genetic material were performed by Polymerase Chain Reaction and RFLP techniques. The remedial measures for treating these bacteria were studied with the help of metabolites obtained from various strains. Int. J. Appl. Sci. Biotechnol. Vol 6(3): 279-284